Strain uses gap junctions to reverse stimulation of osteoblast proliferation by osteocytes. (January 2017) - Suswillo, Rosemary F.L.; Javaheri, Behzad; Rawlinson, Simon C.F.; Dowthwaite, Gary P.; Lanyon, Lance E.; Pitsillides, Andrew A.
Abstract : Identifying mechanisms by which cells of the osteoblastic lineage communicate in vivo is complicated by the mineralised matrix that encases osteocytes, and thus, vital mechanoadaptive processes used to achieve load‐bearing integrity remain unresolved. We have used the coculture of immunomagnetically purified osteocytes and primary osteoblasts from both embryonic chick long bone and calvariae to examine these mechanisms. We exploited the fact that purified osteocytes are postmitotic to examine both their effect on proliferation of primary osteoblasts and the role of gap junctions in such communication. We found that chick long bone osteocytes significantly increased basal proliferation of primary osteoblasts derived from an identical source (tibiotarsi). Using a gap junction inhibitor, 18β‐glycyrrhetinic acid, we also demonstrated that this osteocyte‐related increase in osteoblast proliferation was not reliant on functional gap junctions. In contrast, osteocytes purified from calvarial bone failed to modify basal proliferation of primary osteoblast, but long bone osteocytes preserved their proproliferative action upon calvarial‐derived primary osteoblasts. We also showed that coincubated purified osteocytes exerted a marked inhibitory action on mechanical strain–related increases in proliferation of primary osteoblasts and that this action was abrogated in the presence of a gap junction inhibitor. These data reveal regulatory differences between purified osteocytes derived from functionally distinct bones and provide evidence for 2 mechanisms by which purified osteocytes communicate with primary osteoblasts to coordinate their activity.